Analysis of Miscommunication between Pilot and Air Traffic Control (ATC) and Its Contribution to Flight Incidents - Rizky Arlanda Sihombing; Nunuk Praptiningsih; Yudha Abimanyu (CV. AFDIFAL MAJU BERKAH, 2026)
This study aims to analyze the forms, causes, and impacts of miscommunication between pilots and Air Traffic Controllers (ATC) on flight incidents. The research employs a qualitative descriptive design with a case study approach based on content analysis of official safety reports from KNKT, ICAO, and FAA. Data were analyzed using the Human Factors Analysis and Classification System (HFACS) framework to identify human, environmental, supervisory, and organizational factors. The results indicate that the most common types of communication errors include readback errors, hearback errors, non-standard phraseology, overlapping transmissions, and omission errors. Major contributing factors involve fatigue, high workload, frequency interference, insufficient phraseology training, and weak reporting culture. Miscommunication has been shown to directly contribute to incidents such as loss of separation, airprox, and runway incursions. Recommended mitigation efforts include scenario-based training, implementation of the Safety Management System (SMS) and Just Culture, as well as the use of digital communication technologies such as Controller Pilot Data Link Communication (CPDLC). Effective, clear, and standardized communication remains the cornerstone of aviation safety.